Industrialization and Southern Society, 1877-1984 - Cobb, James C. (James Charles), 1947- (Book collections on Project MUSE., 2004)
In the 1880s, Southern boosters saw the growth of industry as the only means of escaping the poverty that engulfed the postbellum South. In the long run, however, as James C. Cobb demonstrates in this illuminating book, industrial development left much of the South's poverty unrelieved and often reinforced rather than undermined its conservative social and political philosophy. The exploitation of the South's resources, largely by interests from outside the region, was not only perpetuated but in many ways strengthened as industrialization proceeded. The 20th Century brought increasing competi.